Multifunctional vitamin D-incorporated PLGA scaffold with BMP/VEGF-overexpressed tonsil-derived MSC via CRISPR/Cas9 for bone tissue regeneration - So-Yeon Park; Jun-Kyu Lee; Sang-Hyeok Lee; Da-Seul Kim; Ji-Won Jung; Jun Hyuk Kim; Seung-Woon Baek; Seungkwon You; Dong-Youn Hwang; Dong Keun Han (Materials Today Bio)
Guiding endogenous regeneration of bone defects using biomaterials and regenerative medicine is considered an optimal strategy. One of the effective therapeutic approaches involves using transgene-expressed stem cells to treat tissue destruction and replace damaged parts. Among the various gene editing techniques for cells, clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) is considered as a promising method owing to the increasing therapeutic potential of cells by targeting specific sites. Herein, a vitamin D-incorporated poly(lactic-co-glycolic acid) (PLGA) scaffold with bone morphogenetic protein 2 (BMP2)/vascular endothelial growth factor (VEGF)-overexpressed tonsil-derived MSCs (ToMSCs) via CRISPR/Cas9 was introduced for bone tissue regeneration. The optimized seeding ratio of engineered ToMSCs on the scaffold demonstrated favorable immunomodulatory function, angiogenesis, and osteogenic activity in vitro. The multifunctional scaffold could potentially support stem cell in vivo and induce the transition from M1 to M2 macrophage with magnesium hydroxide and vitamin D. This study highlights the improved synergistic effect of a vitamin D-incorporated PLGA scaffold and a gene-edited ToMSCs for bone tissue engineering and regenerative medicine.